2016
DOI: 10.1111/are.13101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined use ofBacillusand molasses on microbial communities in shrimp cultural enclosure systems

Abstract: To assess the effect of addition of probiotics and carbon source on the microbial community structure within the shrimp culture, an enclosure system simulating a high density, intensive aquaculture of Litopenaeus vannamei was set up in Dianbai, Maoming, Guangdong province, China. The phylogenetic profiles of microbial communities in the enclosure system after addition of Bacillus and molasses were studied in the middle and final culture season (on the 45th, 75th and 95th day) using polymerase chain reaction-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Specially, some studies investigated the effect of adding Bacillus spp. to the water in the earthen pond on growth performance and shrimp production (Wang, Xu, & Xia, ), nitrite removal (Song, An, Fu, & Yang, ; Wu et al, ) and microbial community (Hu et al, ). Also, some studies have reported the positive effects of Pediococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, some studies investigated the effect of adding Bacillus spp. to the water in the earthen pond on growth performance and shrimp production (Wang, Xu, & Xia, ), nitrite removal (Song, An, Fu, & Yang, ; Wu et al, ) and microbial community (Hu et al, ). Also, some studies have reported the positive effects of Pediococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bacterial communities in gut flora and rearing water associated with L. vannamei larvae at different healthy statuses have been examined (Zheng et al, ). In addition, functional microorganisms, such as probiotics, impact on the disease and growth of shrimp were also frequently reported (Hu et al, ; Lukwambe et al, ). By contrast, researches focused on the bacterial community associated with jellyfish and razor clam were very little.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, three ways are used for microbial manipulation, including (a) supplementation of exogenous bacteria (Liang et al., ; Wu et al., ; Zhang et al., ), (b) adding the nutrients that benefit growth of the preferred bacteria (Avnimelech, ; Gao, Shan, Zhang, Bao & Ma, ; Xu, Morris & Samocha, ; Yu et al., ; Zheng, Zhang, Qin & Wang, ) and (c) adding exogenous bacteria and nutrients in combination (Hu et al., ). The outcomes of exogenous bacteria in improving production performance and water quality of aquaculture practices are inconsistent.…”
Section: Introductionmentioning
confidence: 99%